(untitled) (Annals of Medical Research, 2021)
Aim: To determine the efficiency of serum amyloid-A (SAA) in predicting preterm premature rupture of membrane (PPROM) and chorioamnionitis in risky cases. Study Design: The study consists of 20 women 26-37 weeks of pregnancy who had PPROM and 20 pregnant women without water breaks. Levels of SAA were determined in maternal venous and umbilical cord blood. Results: SAA values in cord blood and venous blood of mothers with PPROM were higher than in the control group (p0,05). SAA values in the patients with clinical chorioamnionitis (n=9) were significantly higher (p0,05) than both PPROM patients without chorioamnionitis (n=11) and the control group (n=20). Conclusion: In women at risk for PPROM in whom diagnosis cannot be established, blood SSA levels can be used as a marker. Increased SAA values in pregnant women with PPROM who were conservatively treated were considered a marker for chorioamnionitis.